2010
DOI: 10.1161/strokeaha.109.573543
|View full text |Cite
|
Sign up to set email alerts
|

Quality-Adjusted Life Expectancy (QALE) and Loss of QALE for Patients With Ischemic Stroke and Intracerebral Hemorrhage

Abstract: Background and Purpose-Few studies have evaluated the long-term health impact of stroke as categorized into different subtypes. The aim of this study is to quantify the loss of quality-adjusted life expectancy related to ischemic stroke and intracerebral hemorrhage. Methods-The hospital-based cohort, which consisted of 13 194 patients with first-ever stroke onset dates between 1995 and 2007, was classified into lacunar and nonlacunar infarctions and intracerebral hemorrhages. After linking with the National Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 37 publications
5
75
0
Order By: Relevance
“…13 17 20 21 25 33 44 The pooled 5-year survival estimate in three population-based studies13 17 21 was 29.2% (95% CI 25.7 to 32.8; n/N=203/699; I 2 =6.4%; figure 2), but we did not meta-analyse the results of hospital-based studies because of their inconsistency (I 2 =91.9%; figure 2). There was no temporal trend in 5-year survival from years 1983 to 1997 (annual increase of 0.3% per year, 95% CI −0.02 to 0.6, p=0.5).…”
Section: Resultsmentioning
confidence: 99%
“…13 17 20 21 25 33 44 The pooled 5-year survival estimate in three population-based studies13 17 21 was 29.2% (95% CI 25.7 to 32.8; n/N=203/699; I 2 =6.4%; figure 2), but we did not meta-analyse the results of hospital-based studies because of their inconsistency (I 2 =91.9%; figure 2). There was no temporal trend in 5-year survival from years 1983 to 1997 (annual increase of 0.3% per year, 95% CI −0.02 to 0.6, p=0.5).…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for excluding intra-parenchymal or subarachnoid hemorrhagic stroke includes the fact that they make up the minority of stroke type in Jamaica with previous studies showing a prevalence of 11.1% and 5.3%, respectively, while ischemic stroke accounted for majority of stroke type with a prevalence of 83.6% [2]. Also hemorrhagic strokes are associated with higher mortality rates at initial presentation and previous studies have shown no difference in QOL outcomes when comparing these individuals to those with ischemic stroke [28][29][30]. Therefore, the information gained from including this stroke type would be minimal.…”
Section: Study Population and Designmentioning
confidence: 99%
“…Intracerebral hemorrhage (ICH) represents up to 10-15% of all strokes in the United States alone and can result in a greater degree of morbidity, mortality, and loss of quality of life compared to ischemic stroke [1]. However, few improvements in outcome have been realized over the last 20 years, and no proven therapeutic intervention has been developed, as evidenced by recent costly multicenter clinical trials [2,3].…”
Section: Introductionmentioning
confidence: 99%